Seismic performance of CFS strap-braced walls using capacity-based design approach. (November 2020) - Kasaeian, Shahrzad; Usefi, Nima; Ronagh, Hamid; Dareshiry, Saeed
Abstract: Cold-formed steel (CFS) regulations follow capacity-based design approach to ensure that the strap braces act as a ductile element in a seismic force-resisting system. In this paper, bracing system is modified in compliance with the capacity-based design principals which allows energy dissipation of braces through yielding of a fuse element. In this framework, the results of an experimental program on the lateral performance and ductile behaviour of six CFS strap-braced walls are presented. A theoretical approach is then employed to investigate the capacity-based design requirements for the strap-braced walls of this study. Finally, a numerical model is performed for simulation of strap-braced panels with the fuse element. The results indicate the specimens S1-S4 of this study can provide ductile behaviour and are capable of reaching their maximum allowable lateral drift without any undesirable failure. The results also show that strengthening of the brace must be compatible with the strength of the other elements to achieve a ductile response since straps with higher strength can adversely affect the ductility and prevent the wall penal from reaching to the full yielding capacity of the braces. Graphical abstract: Unlabelled Image Highlights: Experimental program on seismic behaviour of CFS strap-braced walls is described. Theoretical approach is implemented to investigate the capacity-based design requirements for CFS strap-braced walls. Numerical modelling is conducted to simulate the ductile behaviour of CFS strap-braced walls with fuse element. Reducing strap cross-section as a fuse element must be in compliance with capacity-based design principals.